Rheological and statistical evaluation of nontraditional lightweight completion fluid and its dependence on temperature - Khalil, M.; Jan, B.M.; Abdul Raman, Abdul Aziz (2011)
This study presents a concise rheological and statistical evaluation of a novel super lightweight completion fluid (SLWCF) and the effect of temperature on its viscosity. Eight rheological models were proposed in order to describe the viscoplastic behavior of the fluid. Based on the results, the fluid is best described both by the Sisko model and the Mizahri-Berk model. These two models are not only able to quantify the relationship between shear rate and shear stress accurately, but also accommodate the physical characteristics of the fluids. On the study of fluid's viscosity dependence on temperature, the result shows that the activation energy decreases with the increases of shear, and its pattern follows a power equation. It could be concluded that viscosity is more sensitive to temperature changes at low shear rate. On the other hand at high shear rate, viscosity seems to be less dependent on temperature. (C) 2011 Elsevier B.V. All rights reserved.